Semantic dementia with ubiquitin-positive tau-negative inclusion bodies - Martin N. Rossor; Tamás Révész; P. L. Lantos; Elizabeth K. Warrington (2000)
Three cases are reported with dementia and ubiquitin-positive but tau-negative inclusion bodies. All patients had a semantic dementia and the clinical details of two of these have been published as the first description of a selective semantic memory impairment. The original diagnosis had been of Pick's disease based on frontotemporal atrophy, but re-examination has revealed ubiquitin-positive but tau-negative inclusions as well as neurites in the frontotemporal cortices and ubiquitin-positive, intracytoplasmic inclusions in the granule cells of the dentate fascia. These inclusions are identical to those reported in association with amyotrophic lateral sclerosis (motor neuron disease), but none were seen in brainstem or spinal cord motor neurons.